Associations Between Lifestyle Factors and Reduced Kidney Function in US Older Adults: NHANES 1999-2016 - Horng-Jinh Chang; Kuan-Reng Lin; Meng-Te Lin; Junn-Liang Chang; Junn-Liang Chang (Frontiers Media S.A., 2021)
Objective: This study aimed to evaluate the associations between lifestyle factors and the estimated glomerular filtration rate (eGFR) levels in older adults by analyzing the United States National Health and Nutrition Examination Survey data (1999-2016).Methods: A total of 10,052 eligible participants were divided into two groups: reduced eGFR group (eGFR < 60 ml/min/1.73 m2) and normal group (eGFR ≥ 60 ml/min/1.73 m2). The primary factors were physical activity, alcohol consumption, smoking, and comorbidities.Results: Multivariable analysis revealed that older age, proteinuria, cardiovascular disease, diabetes, hyperuricemia, and hypertension were significantly associated with higher odds of reduced kidney function. Sufficient physical activity, current alcohol consumption, and being a current smoker were significantly associated with lower odds of reduced kidney function. However, subgroup analysis by sex revealed that the effects of proteinuria, current alcohol consumption, and sufficient physical activity were sex-specific.Conclusion: Several risk and beneficial factors for reduced kidney function in adults aged 65 and above in the United States were identified, but some of them might be sex-specific. Further studies are warranted to confirm these findings in other populations and countries.